A picture's worth a thousand words: a case study of grade 10 English language educators teaching visual literacy - Leask-Smith, Lyn Ann (Rhodes University, Faculty of Education, Department of Education, 2009)
The aim of this research was to better understand teacher's beliefs about visual literacy and to explore how their beliefs influence their teaching practice. In order to investigate this, a case study was conducted that comprised of lesson observations and semi-structured interviews with two secondary school English home language educators. The backdrop to the research was the implementation of the new national curriculum for grade 10. The participants, though well educated and experienced teachers, felt their training had been inadequate in the area of teaching visual literacy and although they acknowledged the importance of visual literacy, it seemed to have a fairly low priority in their actual teaching practice. In particular, very little attention was given to the production of multimodal texts by learners. The reason for this low priority may be related to the requirements of the formal assessment programme as well as limited lesson time in which to cover an extensive curriculum. The research findings would seem to suggest a need for in-service training in this area as well as access to suitable learning support materials and teacher resources.
Keywords: Visual literacy -- Study and teaching (Secondary) -- Case studies; English language -- Study and teaching (Secondary) -- Case studies; Teacher educators -- Training of -- Case studies; English teachers -- Training of -- Case studies; Teachers -- In-service training